Organizational Commitment of the Millennial Generation Workforce in Indonesian Higher Education: Systematic Literature Review - Muhammad Ridlo Zarkasyi (AL-ISHLAH: Jurnal Pendidikan, 2024)
This paper aims to offer a thorough review of research on the factors influencing organizational commitment among the millennial workforce in Indonesian higher education. The review specifically addresses the key questions of identifying the main factors affecting organizational commitment in the millennial workforce in Indonesian higher education and examining how knowledge sharing relates to organizational commitment among these millennial employees. The criteria for selecting the 50 research articles included a requirement that they be peer-reviewed and published in either English or Indonesian. Exclusion criteria were applied to filter out non-peer-reviewed sources and articles not focused on the specified demographic. The articles were sourced from electronic scientific databases, including Google Scholar, Scopus, and Web of Science, using search terms such as "organizational commitment," "millennial workforce," "Indonesian higher education," and "knowledge sharing." The review process involved a systematic analysis of the articles to assess their relevance and quality. Criteria for assessment included the robustness of the research methodology, the significance of the findings, and their contribution to understanding organizational commitment and knowledge sharing. Empirical evidence from the review highlights specific aspects of organizational commitment linked to knowledge sharing, such as the influence of leadership styles, workplace culture, and individual motivation. The paper presents a conceptual framework connecting organizational commitment and knowledge sharing, providing a basis for further research in this field. The findings underscore the need for more research on the impact of organizational commitment on knowledge sharing, particularly within the higher education sector. Enhancing organizational commitment is crucial for fostering knowledge sharing behavior and workplace spirituality, which can lead to improved effectiveness and performance in universities.